Respuesta :
Hi, the quadratic formula is: [tex]\boxed{X= \dfrac{-b \pm \sqrt{b ^{2}-4ac } }{2a}}[/tex]
Values: a = 1; b = - 3; c = -1
Solving:
[tex]X ^{2}-3X-1=0[/tex]
[tex]X= \dfrac{-(-3) \pm \sqrt{(-3) ^{2}-4(1)(-1) } }{2(1)}[/tex]
[tex]X= \dfrac{3 \pm \sqrt{9+4} }{2}[/tex]
[tex]X= \dfrac{3 \pm \sqrt{13} }{2}\ ===\ \textgreater \ \ Answer:\ \boxed{ \textbf{Option\ {C.}}}[/tex]
GOOD LUCK...!!!
Values: a = 1; b = - 3; c = -1
Solving:
[tex]X ^{2}-3X-1=0[/tex]
[tex]X= \dfrac{-(-3) \pm \sqrt{(-3) ^{2}-4(1)(-1) } }{2(1)}[/tex]
[tex]X= \dfrac{3 \pm \sqrt{9+4} }{2}[/tex]
[tex]X= \dfrac{3 \pm \sqrt{13} }{2}\ ===\ \textgreater \ \ Answer:\ \boxed{ \textbf{Option\ {C.}}}[/tex]
GOOD LUCK...!!!